An Investigation to the Performance of Quantized DSSS in Mobile Wireless Communications under AWGN and Multipath Fading Channels - Soudani, Riyadh Jabbar (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper presents an investigation to the performance of quantized direct-sequence spread spectrum system (DSSS) in mobile wireless communications systems. To obtain a real world value (RWV), the DSSS received signal is quantized to different levels of fixed-point values. These modes of quantization are evaluated by calculating BER under different channels environments (AWGN, Rayleigh, and Rician multipath fading). The effect of range of the represented values, the number precision and increasing in quantization noise on the performance of quantized DS in mobile wireless communications is also investigated. Based on simulation results, it is observed that quantized direct-sequence offers a trade-off between complexity and noise rejection compared to non-quantized DSSS and making a good representation of the digitized signals to implement the required DSSS in mobile wireless communications.